Analisis Kebijakan Peraturan Bupati No. 6 Tahun 2019 Di Lingkungan Kabupaten Tapanuli Tengah Dalam Meningkatkan Kinerja Pegawai Di Kelurahan Sibuluan Indah - Aulia Dhuhri; Isnaini Isnaini; Maksum Syahri Lubis (PERSPEKTIF, 2022)
The level of community satisfaction with services from the kelurahan is still relatively low, as can be seen from the many protests from the community against the kelurahan policy. This situation can be seen from the implementation of the work which is still slow so that most of the work cannot be completed on time. This study aims to determine what policies and constraint factors cause the less successful policy of Regent Regulation no. 6 of 2019 concerning Provision of Additional Income for Civil Servants in Central Tapanuli Regency in Improving Employee Performance in Sibuluan Indah Village, Pandan District. The research used was descriptive method, and the data analysis technique used descriptive qualitative. The results of the study show that the TPP policy has not fully succeeded in improving the performance of employees in Sibuluan Indah Village, Pandan District, with the following recommendations: 1) that the Central Tapanuli Regency government needs to revise the TPP policy so that it is more detailed about the elements of performance appraisal, 2) Officials appraisers need to eliminate the influence of personal relationships in making assessments of the performance of subordinates, and 3) The government needs to pay attention to the payment of TPP funds can be made in a timely manner.